Paradox of shortage : food during the Japanese occupation of Singapore - Goh, Xiu Chuan (2018)
Singapore’s state narrative on food shortage during the Japanese Occupation is often characterized by hunger, starvation and even death from starvation. This narration is further enforced by state education such as history textbooks and National Education. However, upon consulting many of the existing oral history interviews, it became obvious that the severity of food shortage has been conflated by the government. This paper aims to fill the literature gap by studying the food economy and food perception of both individuals and the state. The concept of “food” will be examined from a cultural point of view to better understand the importance of culture in shaping one’s food choice and how it shaped the demand for specific food items. This paper argues that sustenance was not the sole motive of food consumption even dire periods of shortage; revealing the inextricable relationship between the culture and caloric duality of food studies.